Transmembrane 4 L Six Family Member 1 Suppresses Hormone Receptor-–Positive, HER2-Negative Breast Cancer Cell Proliferation - Chen, Jie; Zhu, Jin; Xu, Shuai-Jun; Zhou, Jun; Ding, Xiao-Fei; Liang, Yong; Chen, Guang; Lu, Hong-Sheng (Frontiers in Pharmacology, 2022)
Background The prognosis of breast cancer varies according to the molecular subtype. Transmembrane 4 L six family 1 (TM4SF1) exhibits different expression patterns among the molecular subtypes of breast cancer. However, the expression profile of TM4SF1 in hormone receptor HR+HER2- breast cancer remains unclear. Methods TM4SF1 mRNA levels was examined in major subclasses of breast cancer by analyzing The Cancer Genome Atlas (TCGA) datasets. In addition, TM4SF1 protein and mRNA levels in HR+HER2- breast cancer tissue samples were determined using immunohistochemistry and western blot assay. The effect of TM4SF1 on cell proliferation was evaluated using MTT, colony formation, 3D organoid and xenograft models following TM4SF1 overexpression or knockdown. Results TCGA database analysis demonstrated that TM4SF1 was downregulated in breast cancer compared with healthy adjacent breast tissue. In addition, the expression of TM4SF in basal-like 1 and mesenchymal TNBC tissue was higher than that of healthy adjacent breast tissue. Other types, including luminal androgen receptor-positive TNBC tissue, expressed lower levels of TM4SF. Immunohistochemistry and Real-time quantitative PCR assays demonstrated that TM4SF1 protein and mRNA levels were downregulated in HR+HER2- breast cancer tissue compared with healthy adjacent tissue. Moreover, TM4SF1 overexpression reduced the viability of MCF-7 and ZR-75-1 breast cancer cells, whilst reducing the number of colonies and 3D-organoids formed by these cell lines. By contrast, TM4SF1 knockdown led to increased MCF-7 cell proliferation. However, in the TNBC cell line, MDA-MB-231, TM4SF1 silencing reduced cell proliferation. In vivo, TM4SF1 overexpression inhibited MCF-7 xenograft growth in a nude mouse model, which was associated with the downregulation of Ki-67 expression, apoptosis induction and inhibition of the mTOR pathway. Conclusion TM4SF1 is downregulated in HR+HER2- breast cancer and overexpression of TM4SF1 suppresses cell proliferation in this cancer subtype.